1995
DOI: 10.1152/jn.1995.73.2.632
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Y group in the squirrel monkey. II. Contribution of the cerebellar flocculus to neuronal responses in normal and adapted animals

Abstract: 1. The effects of electrical pulse stimulation and temporary pharmacological inactivation of the ipsilateral cerebellar flocculus on the activity of single Y group cells were studied in three alert squirrel monkeys. The extent of the flocculus was mapped by multiunit recording and by electrical pulse train stimulation, which elicited slow eye movement. 2. Single electrical pulse stimulation of the flocculus (0.1-ms constant current, 25-400 microA) resulted in inhibition of all 24 Y cells examined. The inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(68 citation statements)
references
References 0 publications
3
65
0
Order By: Relevance
“…Thus it seems unlikely that projections from EH neurons to the abducens nucleus (Scudder and Fuchs 1992) impact VOR function in this condition. This proposal is consistent with prior studies that have shown that inactivation of the flocculus has little effect on the behavioral VOR gain (Partsalis et al 1995;Zhang et al 1995a,b). We suggest that the contribution of EH neurons becomes significant in situations where the VOR gain must be modified such as during adaptation following spectacle-induced motor learning (Lisberger 1994;Lisberger et al 1994a), and vestibular injury.…”
Section: Floccular Inputs To Eh Neuronssupporting
confidence: 92%
“…Thus it seems unlikely that projections from EH neurons to the abducens nucleus (Scudder and Fuchs 1992) impact VOR function in this condition. This proposal is consistent with prior studies that have shown that inactivation of the flocculus has little effect on the behavioral VOR gain (Partsalis et al 1995;Zhang et al 1995a,b). We suggest that the contribution of EH neurons becomes significant in situations where the VOR gain must be modified such as during adaptation following spectacle-induced motor learning (Lisberger 1994;Lisberger et al 1994a), and vestibular injury.…”
Section: Floccular Inputs To Eh Neuronssupporting
confidence: 92%
“…Repetitive climbing fiber stimulation, which causes floccular shutdown, had no effect on changes in VOR gain that were learned over several days (Luebke and Robinson 1994), suggesting that the cerebellar cortex does not participate in the longterm storage of motor memory. Unilateral inactivation of the lateral vestibulocerebellum in monkeys also did not abolish longterm memory in the vertical VOR (Partsalis et al 1995). However, in the goldfish, McElligott and coworkers (McElligott et al 1998) were able to completely abolish changes in gain that had been learned within the previous few hours, by infusing lidocaine into the flocculus.…”
Section: Consolidation Of Vor Motor Memorymentioning
confidence: 96%
“…More specifically, during visual/vestibular stimuli that increase VOR gain and during head movements in the dark in animals with a learned high VOR gain, Purkinje cells increase their firing during contraversive head movements. During visual/vestibular stimuli that drive decreases in VOR gain and during head movements in the dark in animals with a learned low VOR gain, the Purkinje cells increase their firing during ipsiversive head movements (Dufosse et al 1978;Lisberger and Fuchs 1978;Miles et al 1980a,b;Watanabe 1984;Lisberger et al 1994;Partsalis et al 1995).…”
Section: Candidate Neural Mechanisms For the Extinction-like Process mentioning
confidence: 99%